ANALYSIS OF THE IMPLEMENTATION OF QURAN RECITATIONS FOR MADRASAH STUDENTS TSANAWIYAH AL WASHLIYAH PAKAM VILLAGE MEDANG DERAS DISTRICT BATU BARA REGENCY - Muliatno; Rio Ari Waldani (RADJA PUBLIKA, 2022)
Type This research is a type of qualitative descriptive research.The results of the research in this thesis,Extracurricular implementationRecitations at Madrasah Tsanawiyah Al Washliyah Desa Pakam place more emphasis on theoretical and practical elements, this is compatibility in fostering the art of reading the Koran, meaning that it is appropriate when implemented or applied to the field of reading the Koran, that is, it will always implement and develop these strategies in order to further enhance student learning optimally . Based on the results of interviews with the head of the madrasa and the recitation extracurricular supervisor, there are inhibiting factors, namelylow student motivation, less gifted student problems, fales voice problems, lack of time for activities as well as, less varied learning methods. The implementation of recitations of the Koran at Madrasah Tsanawiyah Al Washliyah Pakam Village, Medang Deras District was held in the framework of introducing knowledge to students who lack mastery and as a trigger to deepen how to read the Koran properly and correctly. The recitation extracurricular at Madrasah Tsanawiyah Al Washliyah Desa Pakam was the idea of ​​the vice head of the madrasa namely. This activity was formed with the aim that the students of Madrasah Tsanawiyah Al Washliyah Pakam Village can read the Koran properly and correctly.